Science centre engagement on visitor personal connection - Baniyamin, Nurhaya; Abdul Rahim, Zaiton (USA Passion Development Sdn. Bhd., 2018)
Museum exhibition environment provides experiential learning through its messages to influence knowledge, attitudes and learning behaviours of visitors. Connections in visitors' cognitive, affective, emotional and physiological responses play a beneficial role in museum visits. The research focuses on how science centre as part of a museum discusses various methodological approaches to encourage visitor into having a response. The review highlights multiple learning theories underpinning how visitors learn and how these theories impact a museum’s exhibition design efforts. Using the experience of selected Science Centres as primary case-studies, this paper examines different perspectives and methodological approaches. Nurturing visitor interest through visitor personal connection represents an essential recurring concept which strikes at the core of the exhibition design process. Visitors act as celebrants of science information in an edutainment context, motivated by a quest for social and enlightening experiences.